Methane uptake responses to heavy rainfalls co-regulated by seasonal timing and plant composition in a semiarid grassland - Zheng, Zhenzhen; Wen, Fuqi; Li, Congjia; Guan, Shuntian; Xiong, Yunqi; Liu, Yuan; Qian, Ruyan; Lv, Mengbo; Xu, Shaorui; Cui, Xiaoyong; Wang, Yanfen; Hao, Yanbin; et al. (Frontiers in Ecology and Evolution, 2023)
Global warming caused heavy rainfalls are increasing widespread in the future. As the second greenhouse gas, the biological processes of methane (CH4) uptake would be strongly affected by heavy rainfalls. However, how seasonal timing and plant composition affect CH4 uptake in response to heavy rainfalls is largely unknown. Here, we conducted a manipulative experiment to explore the effects of heavy rainfall imposed on middle and late growing season stage on CH4 uptake of constructed steppe communities including graminoid, shrub and their mixture in Inner Mongolia, China. The results of mixed effect model showed that both heavy rainfalls decreased CH4 uptake. Nevertheless, the effect magnitude and the pathways were varied with seasonal timing. Relatively, the late heavy rainfall had larger negative effects. Structural equation model analyses suggested that late heavy rainfall decreased CH4 uptake through high soil water content (SWC) induced low diffusivity, pomA abundance and NH4+-N content while middle heavy rainfall decreased CH4 uptake only by increasing SWC. Additionally, above ground biomass (AGB) had negative effects on CH4 uptake under both heavy rainfalls. Additionally, plant composition not only affected CH4 uptake but also regulated CH4 uptake in response to heavy rainfalls. Late heavy rainfall had less negative effect on CH4 uptake in graminoid community than in other two communities, in coincidence with less reduction in NH4+-N content and less increase in SWC and AGB. In contrast, we did not observe obvious difference in effects of middle heavy rainfall on CH4 uptake across three communities. Our findings demonstrated that magnitude and pathways of heavy rainfall effects on CH4 uptake strongly co-regulated by seasonal timing and plant composition.